2018
DOI: 10.1001/jamadermatol.2017.6197
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Early Dermatology Consultation for Inpatients Diagnosed With Cellulitis

Abstract: IMPORTANCE Many inflammatory skin dermatoses mimic cellulitis (pseudocellulitis) and are treated with antibiotics and/or hospitalization, leading to unnecessary patient morbidity and substantial health care spending. OBJECTIVE To evaluate the impact of early dermatology consultation on clinical and economic outcomes associated with misdiagnosed cellulitis. DESIGN, SETTING, AND PARTICIPANTS This prospective cohort study enrolled patients with presumed diagnosis of cellulitis in the emergency department, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
68
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 23 publications
1
68
0
4
Order By: Relevance
“…Other studies have shown that immediate consultation, within 24 h of hospitalization, led to shorter duration of treatment and decreased length of stay. 18,19 Figure 1 (a-j). This graph summarizes the collected data, including age at time of consultation (a), reason for admission (b), admission length prior to dermatology consult (c), number of inpatient visits by dermatology consultant (d), primary team (e), dermatology recommended testing (f), number of dermatologic diagnoses (g), whether or not the primary team followed dermatology's treatment plan (h), whether outpatient dermatology follow-up was needed after discharge (i) and whether or not the patient was lot to dermatology follow-up after discharge (j).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that immediate consultation, within 24 h of hospitalization, led to shorter duration of treatment and decreased length of stay. 18,19 Figure 1 (a-j). This graph summarizes the collected data, including age at time of consultation (a), reason for admission (b), admission length prior to dermatology consult (c), number of inpatient visits by dermatology consultant (d), primary team (e), dermatology recommended testing (f), number of dermatologic diagnoses (g), whether or not the primary team followed dermatology's treatment plan (h), whether outpatient dermatology follow-up was needed after discharge (i) and whether or not the patient was lot to dermatology follow-up after discharge (j).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies show the admitting hospital service misdiagnoses skin disease at rates of between 45% and 78% of the time . Length of stay was reduced with inpatient consultation for dermatological disease by 2.64 days in one study and 2.1 days in another study . The same study by Milan‐Nejad et al .…”
mentioning
confidence: 77%
“…also found a decrease in hospital readmission rates in this cohort of patients. Li et al . used their study results to attempt to quantify the economics of dermatology consultation, and found that employing early and universal dermatology consultation for presumed cellulitis could save up to 256 000 inpatient days and $210 million annually in the U.S.A. alone.…”
mentioning
confidence: 99%
“…9 It is important to recognize pseudocellulitis early as they are com- showed that early consultation by dermatologists for patients with presumed cellulitis is a cost-effective intervention to reduce inappropriate antibiotic use and hospitalization. 10 This intervention may be a worthwhile consideration for hospitals with sufficient dermatological support.…”
mentioning
confidence: 99%